1994
DOI: 10.1002/pen.760341011
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and energy absorption of polymer foams as a function of 2‐D indenter and absorber geometries

Abstract: Amherst. Massachusetts 01 003Two-dimensional indenters (flat plate and cylinder) were used to compress rectangular and trapezoidal foam energy absorbers as a function of polymer, foam density, and thickness. An increased deformation volume formed when the indenter contact area was less than the foam absorber area, resulting in both increased energy absorption and stress transmitted to the indenter (i.e., "load spreading"). The deformation volume was trapezoidal, not prismatic, and was characterized by the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Early work on the indentation of foams has suggested that it is controlled to a large extent by its compressive strength [1,2]. Preliminary work on the indentation of foams was presented by Andrews et al [3], Onck et al [4], Gibson and Ashby [5], Tulliani et al [6], Stupak and Donovan [7] and Prakash et al [8]. The average indentation pressure was reported as a function of indenter geometry and contact area, with limited experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Early work on the indentation of foams has suggested that it is controlled to a large extent by its compressive strength [1,2]. Preliminary work on the indentation of foams was presented by Andrews et al [3], Onck et al [4], Gibson and Ashby [5], Tulliani et al [6], Stupak and Donovan [7] and Prakash et al [8]. The average indentation pressure was reported as a function of indenter geometry and contact area, with limited experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…During the impact process, the contact area between the legform and the bumper increases as the legform intrusion increases. Stupak and Donovan 14 addressed the local deformation issue and studied its effects on the impact energy absorption. Some data on the vehicle's front-end stiffness calculated from vehicle's frontal impact tests 15 are available.…”
Section: Contact Characteristics Of the Legform-to-bumper Impact Testmentioning
confidence: 99%
“…Stupak and Donovan [13] studied non-linear deformation mechanisms and energy absorption capacities of two-dimensional test specimens of cellular foam materials subjected to indentation.…”
Section: Introductionmentioning
confidence: 99%